Layoff decisions from the technology industry: Why employers are still making the same mistakes after all these years and lessons they should have learned - Tan, Adrian; Chong, Nik (2024)
The waves of layoffs globally in the technology industry are cause for concern from a humanistic perspective. Although layoffs are not uncommon in any industry, the issue is important but often neglected in terms of employee well-being. Leveraging on the technology industry as a context, the focus of this study is to explore the executive decision-making process for a layoff decision and explore the reasons why employers are still committing the same blunders when deciding on layoffs. Through the conduct of web-based research, reports of layoffs from multiple online mass media sources of 20 prominent technology companies were analyzed. The Gioia methodology was used to uncover the aggregate influencing reasons for layoffs. These reasons were further meta-analyzed for exploration of the reasons behind such poorly justified layoff decisions, managerial implications and lessons employers should have learned from the layoff decisions. The analysis identified three key elements which influence a layoff decision, namely the enactment of business competitive strategies, the pursuit of business sustainability and safeguarding of shareholder interests, and misjudgments in business decisions of the organization leaders. Our research reinvigorates a call to action to responsibly and morally consider how management decisions impact on the emotional and personal wellbeing of those being laid off and those remaining with the company. This research contributes to a deeper understanding of the challenges faced by companies during layoffs and provides 1 actionable insights for improving decision-making to mitigate the effects of layoffs on employees. The study also contributes to the promotion of the decent work agenda of the United Nations Sustainable Development Goals.